Dinámicas diplomáticas regionales en el Centenario de la Batalla de Ayacucho: Entre la diplomacia cultural y el realismo político (1922-1924) - Nieto Minaya, Willy Félix (2024)
This research aims to analyze South American diplomatic dynamics in the context of the preparations for the centennial celebration of the Battle of Ayacucho, between 1922 and 1924. It is argued that the Peruvian state pursued a strategy of cultural diplomacy to gain influence and foster goodwill with neighboring countries by leveraging the celebration of a continental commemoration. The ultimate goal of this maneuver was to secure international support for its foreign policy objectives, primarily centered on the dispute with Chile over the regions of Tacna and Arica. However, as a secondary point, it is argued that these regional dynamics were marked by persistent mistrust and tensions among South American countries, which undermined many of the cultural diplomatic convergence initiatives, prioritizing aspects aligned with a logic of political realism.